The Diagnostic Accuracy of MRI to Evaluate Acute Lisfranc Joint Injuries: Comparison With Direct Operative Observations. Issue 1 (January 2022) - Kitsukawa, Kaoru; Hirano, Takaaki; Niki, Hisateru; Tachizawa, Natsuki; Mimura, Hidefumi
Background: Early diagnosis is important in patients with Lisfranc joint injury to avoid subsequent complications. As the ligaments in the Lisfranc joint are relatively small and course obliquely, isotropic 3-dimensional (3D) magnetic resonance imaging (MRI) can be beneficial to evaluate ligament injury. The purpose of this study was to investigate the diagnostic accuracy of MRI, including isotropic 3D MRI for acute injury of the Lisfranc joint, especially of the interosseous C1-M2 ligament (Lisfranc ligament), the dorsal C1-M2 ligament (dorsal ligament), and the interosseous C1-C2 ligament, compared with direct operative observations. Methods: This retrospective review identified 27 patients who had undergone MR examination for acute Lisfranc joint injury followed by surgery. We reviewed the operative reports that described the Lisfranc, dorsal, and interosseous C1-C2 ligaments. All patients underwent an MRI, including a 2D oblique plane image parallel to the Lisfranc ligament and an isotropic 3D MRI. An image analysis of the integrity of the 3 ligaments and other associated injuries was performed. The diagnostic accuracy of MRI was analyzed using operative findings as a reference standard. Results: Lisfranc and dorsal ligament injuries were identified on MRI in all patients. MRI depicted disruption of the interosseous C1-C2 ligament in 12 patients. MRI diagnostic accuracy for detection of Lisfranc, dorsal, and interosseous C1-C2 ligaments was 100% (95% CI 0.82-1.0), 74% (95% CI 0.54-0.89), and 70% (95% CI 0.50-0.86), respectively. Conclusion: MRI with oblique planes parallel to the Lisfranc ligament and isotropic 3D MRI was reliable for detecting Lisfranc ligament injury, whereas MRI findings of the dorsal and interosseous C1-C2 ligaments were less consistent with operative observations. Level of Evidence: Level IV, case series.